Relasi antara Manusia dan Lingkungan Alam - Daud Effendy AM (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
Human beings and the environment are entities whose existence is natural and ordained. Naturally, a relationship has been established between them since the creation. The quality of the relationship between humans and the environment is determined by the quality of human thought, behavior, and conduct within their surroundings. The standard for evaluating the goodness or badness of this relationship is not solely determined by humans unilaterally, but by an absolute standard, which is the law of God (Sunatullah). This is a consequence of humans being chosen and appointed as stewards of Allah in maintaining the balance of life on Earth. This writing explains the intended relationship, which is capable of building a holistic system of righteousness to achieve peace and prosperity blessed by the pleasure of Allah SWT.